Co3O4/SiO2 Nanocomposites for Supercapacitor Application - Ali, Gomaa A. M.; Fouad, Osama A.; Makhlouf, Salah A.; M. M., Yusoff; K. F., Chong (Springer Link, 2014)
In this study, Co3O4/SiO2 nanocomposites have been successfully synthesized by citrate–gel method by utilizing SiO2 matrix for Co3O4 embedment. Spectroscopy analyses confirm the formation of high crystalline Co3O4 nanoparticles; meanwhile, microscopy findings reveal that the Co3O4 nanoparticles are embedded in SiO2 matrix. Electrochemical properties of the Co3O4/SiO2 nanocomposites were carried out using cyclic voltammetry (CV), galvanostatic charge–discharge, and electrochemical impedance spectroscopy(EIS) in 5 M KOH electrolyte. The findings show that the charge storage of Co3O4/SiO2 nanocomposites is mainly due to the reversible redox reaction (pseudocapacitance). The highest specific capacitance of 1,143 F g−1 could be achieved at a scan rate of 2.5 mV s−1 in the potential region between 0 and 0.6 V. Furthermore, high-capacitance retention (>92 %) after 900 continuous charge–discharge tests reveals the excellent stability of the nanocomposites. It is worth noting from the EIS measurements that the nanocomposites have low ESR value of 0.33 Ω. The results manifest that Co3O4/SiO2 nanocomposites are the promising electrode material for supercapacitor application.